ChemInform Abstract: Block Copolymer Synthesis by Controlled/Living Radical Polymerization in Heterogeneous Systems. Issue 44 (13th October 2016) - Jennings, J.; He, G.; Howdle, S. M.; Zetterlund, P. B.
Abstract: Review: 280 refs.